Writing the Black Decade: Conflict and Criticism in Francophone Algerian Literature - Ford, Joseph (Lexington Books, 2021)
Writing the Black Decade: Conflict and Criticism in Francophone Algerian Literature examines how literature—and the way we read, classify, and critique literature—impacts our understanding of the world at a time of conflict. Using the bitterly-contested Algerian Civil War as a case study, Joseph Ford argues that, while literature is frequently understood as an illuminating and emancipatory tool, it can, in fact, restrain our understanding of the world during a time of crisis and further entrench the polarized discourses that lead to conflict in the first place. Ford demonstrates how Francophone Algerian literature, along with the cultural and academic criticism that has surrounded it, has mobilized visions of Algeria over the past thirty years that often belie the complex and multi-layered realities of power, resistance, and conflict in the region. Scholars of literature, history, Francophone studies, and international relations will find this book particularly useful.